Stratégies d’intégration et de support en santé mentale des immigrants francophones au Canada anglais. - Archambault, Hélène; de Moissac, Daniel; Tempier, Raymond (Minorités linguistiques et société / Linguistic Minorities and Society, 2024)
Résumé Cet article explore les stratégies d’intégration au système de santé telles que proposées par des personnes immigrantes francophones au sein de communautés francophones en situation minoritaire au Canada (CFSM). Une recherche qualitative par entrevues semi-dirigées a été menée dans trois villes canadiennes auprès de soixante personnes adultes immigrantes ou réfugiées. Centrées sur les représentations des personnes immigrantes quant aux services de soutien en santé mentale, diverses stratégies ont été dégagées. La préparation prémigratoire et le regroupement des informations sous un guichet unique semblent contribuer à une intégration réussie. L’appui des organismes communautaires et des autorités religieuses est bénéfique pour le soutien informationnel et socioémotionnel des nouveaux arrivants, ayant des retombées positives sur leur bien-être et leur capacité de s’intégrer à leur nouveau milieu de vie. Mots-clés : immigration, francophones, intégration, système de santé, stratégies Abstract This article explores healthcare integration strategies proposed by Francophone immigrants within Francophone minority communities (FMCs) in Canada. A qualitative study using semi-structured interviews was conducted in three Canadian cities with sixty adult immigrants and refugees. Focusing on immigrants’ perceptions of mental health support services, various strategies were identified. Pre-migration preparation and centralizing information seem to contribute to successful integration. The support of community organizations and religious authorities is beneficial for the socio-emotional and information support of newcomers, having a positive impact on their well-being and their ability to integrate into their new living environment. Keywords: immigration, Francophones, integration, healthcare, strategies

Pratique # 22 : Bien vieillir chez soi / Soutien à domicile (pancanadienne) - Benoît, Josée; Michel, Jean Nephetaly (2021)

Bien dans notre peau: Élaboration d’un outil de diagnostic pour informer la conception et l’évaluation de services et partenariats sécuritaires, inclusifs et équitables pour toute personne 2ELGBTQ+ d’expression française au Manitoba - Courcelles, Rémi; Hardy, Stephan; Prada, Kevin (Santé Canada, 2023)

Healthcare Service Utilization and Perceived Gaps: The Experience of French-Speaking 2S/LGBTQI+ People in Manitoba - de Moissac, Danielle; Prada, Kevin; Gueye, Ndeye Rokhaya; Avanthay-Strus, Jacqueline; Hardy, Stephan (Healthcare Policy, 2024)
Ethnolinguistically diverse 2S/LGBTQI+ (two-spirit, lesbian, gay, bisexual, transgender, queer and intersex) populations have unique healthcare needs and experience health inequities compared to their cisgender or heterosexual peers. This community-based participatory study sought to describe the profile and healthcare needs and experiences of official language minority French-speaking 2S/LGBTQI+ adults in Manitoba. Participants (N = 80) reported that gender and sexual identity were often concealed from service providers; many respondents faced discrimination based on their ethnolinguistic and sexual identities. Service gaps are identified pertaining to mental and sexual health; locating 2S/LGBTQI+-friendly, patient-centred care in French is difficult. Policy and practice should address systemic inequity and discrimination experienced by this equity-seeking population.

Practice #28: Access to Resources in the Community (ARC): A social prescribing and navigation model (Ontario) - Ibrahim, Nour; Benoît, Josée; Savard, Jacinthe (2025)

Pour un accueil en santé des personnes immigrantes francophones au Nunavut - état de situation - Réseau Santé en français au Nunavut (2021)

À la rencontre des communautés acadiennes et francophones et de leurs enjeux en santé - Réseau Santé Nouvelle Écosse (Réseau santé en français de Nouvelle-Écosse, 2021)

Évaluation de la mise en œuvre de services en français en contexte minoritaire : développement d’un questionnaire sur l’expérience des usagers - Sauvé-Schenk, K; Savard, Jacinthe; Savard, Sébastien; Prud’homme, Denis; van Kemenade, Solange; Le Callonnec, L; Pignac, S (2022)

Pratique # 10 : Les points de service satellites (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Pratique # 11 : The Information and Support Guide for Caregivers (Québec) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Pratique # 12 : Les Lunchs-causeries au Centre de services communautaires Vanier (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Pratique # 14 : Les Foires d’information de la Fédération des aînés et des retraités francophones de l’Ontario (FARFO) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Pratique # 27 : Accueil centralisé (Centre francophone du Grand Toronto, Ontario) - van Kemenade, Solange; Benoît, Josée; Savard, Sébastien; Savard, Jacinthe (2025)

Pratique # 23 : Navigateur francophone du système de santé (Terre-Neuve-et-Labrador) - van Kemenade, Solange; Michel, Jean Nephetaly; Savard, Jacinthe; Benoît, Josée (2021)